Comparison of the effects of platelet concentrates produced by high and low-speed centrifugation protocols on the healing of critical-size defects in rat calvaria: a microtomographic and histomorphometric study. (17th November 2022) - da Silva, Lucia Moitrel Pequeno; Sávio, Débora de Souza Ferreira; de Ávila, Felipe Correa; Vicente, Raphael Martini; Reis, Gabriel Guerra David; Denardi, Ricardo Junior; da Costa, Natacha Malu Miranda; Silva, Pedro Henrique Felix; Mourão, Carlos Fernando de Almeida Barros; Miron, Richard J.; Messora, Michel Reis
Abstract: The current study evaluated the healing of critical-size defects (CSD) created in rat calvaria treated with platelet concentrates produced by high-speed (Leukocyte- and Platelet-Rich Fibrin - L-PRF) and low-speed (Advanced Platelet-Rich Fibrin - A-PRF) protocols of centrifugation. Twenty-four rats were distributed into three groups: Control, L-PRF, and A-PRF. Five mm diameter CSD were created on the animals' calvaria. The defects of the L-PRF and A-PRF groups were filled with 0.01 ml of L-PRF and A-PRF, respectively. The control group defects were filled with a blood clot only. All animals were euthanized on the 35th postoperative day. Histomorphometric and microtomographic analyses were then performed. The L-PRF and A-PRF groups had significantly higher bone volume and neoformed bone area than those of the control group and lowered bone porosity values (p < .05). No significant differences were observed between A-PRF and L-PRF groups for the analyzed parameters. Therefore, it can be concluded that i) L-PRF and A-PRF potentiated the healing of CSD in rat calvaria; ii) high and low-speed centrifugation protocols did not produce PRF matrices with different biological impacts on the amount of bone neoformation.